The mitochondrial aldehyde dehydrogenase OsALDH2b negatively regulates tapetum degeneration in rice - Xie, Xianrong (Journal of experimental botany, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of the Society for Experimental Biology.